Organize your life - Mulvey, Kelsey (Hearst Home, 2024)
Decluttering your home has never been easier with this step-by-step action plan. Plus, hundreds of genius tricks help you create a calm and tidy life. Often the hardest part of organizing is getting started. This attractive book from the experts at Good Housekeeping breaks down your decluttering to-do list into smaller zones so you can tidy up and whip your home into shape. Whether you're looking to take on every room in the house or focus on trouble spots (like your linen closet and that junk drawer!), this step-by-step action plan will help you decide what to keep and what to let go, as well as give you neat ideas for putting every space and every room in order...and to keep them that way. With 5-minute tidy-up projects or a 28-day declutter challenge and beautiful photographs throughout, you'll unlock the secrets to an organized home. Inside you'll find how to: Divide your organizing projects into zones to make them manageable; Clear out your closets; Dejunk the junk drawer-for good!; Maximize space in the fridge, freezer and pantry; Free up overstuffed nooks and crannies; Boost bathroom storage. With inspiring yet practical advice from the home experts at Good Housekeeping, you'll create order in your home and transform your life.